2019
DOI: 10.1167/iovs.18-26444
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nonexudative Age-Related Macular Degeneration Diagnosis Among Medicare Beneficiaries With Rheumatoid Arthritis

Abstract: Purpose AMD is the leading cause of blindness in the United States. The role of secondary inflammatory disease on AMD progression is largely unknown. Here we investigate the association between AMD and rheumatoid arthritis (RA), using MarketScan data for patients aged ≥65 years on Medicare. Methods Baseline data were extracted for subjects with at least two International Classification, Ninth Revision (ICD-9) diagnosis codes of RA and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
4
10
0
Order By: Relevance
“… 56 In addition to genetics and a healthy lifestyle, individuals who live longer lives are found to have increased levels of anti-inflammatory markers, while increased proinflammatory markers are associated with increased disease (as reviewed by Franceschi 57 ). Our patient database analysis, 23 as well as studies performed by others, observed increased number of AMD cases in the presence of systemic disease, suggesting a role for inflammaging in AMD risk and pathogenesis.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“… 56 In addition to genetics and a healthy lifestyle, individuals who live longer lives are found to have increased levels of anti-inflammatory markers, while increased proinflammatory markers are associated with increased disease (as reviewed by Franceschi 57 ). Our patient database analysis, 23 as well as studies performed by others, observed increased number of AMD cases in the presence of systemic disease, suggesting a role for inflammaging in AMD risk and pathogenesis.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, we identified an increased risk of dry AMD diagnosis among patients with rheumatoid arthritis (RA), along with an earlier time of diagnosis, through retrospective analysis of a Medicare patient database. 23 This study also identified an increased risk of AMD among female patients with RA compared to males. While reports linking an increased incidence of AMD among females in the general population are conflicting, a higher prevalence of females (65%) to males (35%) is diagnosed with AMD according to the 2010 National Eye Institute consensus.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…These circumstances have led to a general interest in markers of chronic low‐grade inflammation in relation to diseases with a complex pathogenesis and where ageing is an important risk factor, such as neurodegenerative disease, inflammatory diseases, cancer and AMD. Indeed, several studies find an epidemiological association between these diseases (Tsai et al 2015; Bak et al 2017; Lin et al 2017; Singh & Cleveland 2018; Hamedani et al 2019; Schnabolk et al 2019). Perhaps the most well‐studied cytokine in the context of chronic low‐grade inflammation is interleukin‐6 (IL‐6) (Bruunsgaard 2006).…”
Section: Introductionmentioning
confidence: 99%